Determinants of Gen Z Tourists' Intentions to Visit Coastal Areas: The Role of Attractiveness, Price Perception, and Tourism Amenities - Andre Mickael; Yustisia Kristiana; Nurisa Anggraeny Sidabutar (International Journal of Islamic Business and Management Review, 2025)
The issue surrounding fluctuating visit intentions and environmental quality in coastal destinations prompted this study, which aims to examine the determinants of Gen Z tourists' intentions to visit coastal areas in Tangerang Regency, integrated with the influence of attractiveness, price perception, and tourism amenities. This study used a quantitative approach using a Likert scale questionnaire given to 215 Gen Z respondents. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that attractiveness, price perception, and tourism amenities positively impact the intention of Gen Z tourists to visit. The results indicate that natural beauty, unique features, and comfort are the main factors driving Generation Z’s intention to visit coastal destinations. Adequate facilities, such as sanitation, sewage systems, and parking areas, enhance visitor experiences and support sustainable tourism. However, challenges remain, including environmental degradation, inappropriate entrance fees, and insufficient infrastructure that hinder sustainability.